Studi Kasus: Dinamika Psikologis Anak Angkat yang Mengalami Gangguan Depresi Mayor Tingkat Berat dengan Fitur Melankolis dan Psikotik - Elvina Febriyani Chandrawijaya; Taufik Akbar Rizqi Yunanto (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
Disturbances in family structure and violence against children are social factors that can trigger depressive disorders. Major depressive disorder is a serious health condition and relate to self-harm attempts that can lead to suicidal ideation. This study aims to determine the psychological dynamics of an adopted child who has a major depressive disorder. This research uses a case study method with qualitative approach. Participant in this study is one person (N=1), a 22-year-old student who had mayor depressive disorder with melancholy and psychotic features. This study will use interview, observation and several psychological test tools as assessment techniques in writing participant dynamics. The results of this study indicate that partisipant’s condition was motivated by stressful life events, lack of affection and acceptance from the family environment, avoidant coping strategies and negative views of self, world and future.